ANALISIS VITAMIN C BUAH SRIKAYA (ANNONA SQUAMOSA) DALAM MENINGKATKAN IMUNITAS TUBUH PADA MASA PANDEMI COVID-19 - Jumriana Rahayu; Edi Kurniawan; Asregi Asril (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2022)
Vitamin C is one of the vitamins that the body needs to increase immunity in warding off all forms of disease. One of the fruits that contain vitamin C is srikaya fruit. Srikaya fruit is a plant belonging to the genus Annona originating from the tropics. Srikaya fruit is analyzed for its vitamin C content in order to increase the immunity of the community during the COVID-19 pandemic. The method used is a laboratory experiment with the iodometric method. The result is that srikaya fruit contains a fairly high amount of vitamin C, with the average vitamin C levels in the srikaya fruit sample being 2.58%, 2.503% and 2.66%, respectively, while the average vitamin C content in the srikaya fruit sample is 2.581%. And during this pandemic, we should consume a lot of food and fruit with vitamin C to increase the body's immunity, so that it can be developed to the next stage of further and more effective research.